Respiratory Disorders and Lung Function Impairments of the Scavengers in Bantar Gebang, Bekasi - Dita Kurnia Sanie; Agus Dwi Susanto; Fahrial Harahap (Jurnal Respirologi Indonesia, 2019)
Background: The workers in the landfill have high risk of health problems. The prevalence of respiratory disorders and lung function increases in waste collection workers. There has been no data on respiratory disorders and lung function in scavengers, especially in Bantar Gebang, Bekasi. Methods: This study used a cross-sectional design to the scavengers who work and live in Ciketing Udik, Bantar Gebang, Bekasi. Conducted in January-March 2015, doing interview with questionnaires, and spirometry examination. Results: The number of samples that suitable with the inclusion criteria are 108 subjects. Respiratory disorders are 92 subjects (85.2%). The respiratory disorders consist of 73 subjects with chronic cough, 65 subjects due to shortness of breath, 57 with phlegm and 19 wheezing. Lung function impairments consist of 18 (16.7%) subjects in the form of mild obstruction 3 (2.8%) subjects, mild restriction 11 (10.2%) subjects and mixed 4 (2.8%) subjects. Results of the analysis show that there is a significant relationship between duration of working with respiratory disorders and lung function impairments. Conclusion: There is respiratory disorders and lung function impairments of the scavengers in Bantar Gebang, Bekasi. (J Respir Indo 2019; 39(2): 70-8)